Impact of electronic health record technology on the work and workflow of physicians in the intensive care unit. Issue 8 (August 2015) - Carayon, Pascale; Wetterneck, Tosha B.; Alyousef, Bashar; Brown, Roger L.; Cartmill, Randi S.; McGuire, Kerry; Hoonakker, Peter L.T.; Slagle, Jason; Van Roy, Kara S.; Walker, James M.; Weinger, Matthew B.; Xie, Anping; et al.
Highlights Post-EHR, all physicians spent more time on clinical review and documentation. Residents switched tasks more often after EHR implementation, attendings less. Temporal flow of tasks changed after EHR implementation. No changes observed in conversation or physical care of the patient.